Hydraulic‐Mechanical Properties of Unsaturated Granite‐Weathered Residual Soil in Korea - Pham, Khanh (2020)
This study performed a series of experiments to examine the hydraulic‐mechanical properties of granite‐weathered residual soil in the Korean Peninsula. Particular attention was paid to the soil‐water characteristic curve (SWCC) and shear strength under various stress states and matric suction levels. The experimental results indicated the decisive influence of the stress state on the SWCC, notably in the low range of matric suction. In addition, the evolution of shear strength with suction became significant under high net confining stress. The effective stress using the stress‐independent SWCC could not describe the actual mechanical behaviors of the unsaturated soil. The relevant effective stress for the granite‐weathered residual soil in consideration was then proposed. Next, a numerical framework for strength analysis with infiltration was developed to manifest the practical applications of the experimental results. The analysis results revealed the potential failure mechanisms of the geotechnical infrastructures induced by rainfall. Ignoring the contribution of matric suction may lead to overly conservative outcomes and cannot capture the realistic performance of soil under the rainfall condition. Moreover, the stress‐dependent hydraulic properties are suggested for application in strength analysis for the safer design of geotechnical infrastructure.